The self-built city: theorizing urban design of informal settlements. (15th July 2019) - Pojani, Dorina
Abstract : Purpose: While a substantial amount of study of informal settlements has been undertaken, they remain largely unstudied in terms of urban form. In this analysis, the purpose of this paper is to set forth a conceptual framework, which considers the context in which informality takes place, the settlement itself, the houses contained therein, the dwellers of those houses and the process through which a settlement is designed and transformed over time. Design/methodology/approach: This is a literature review. Findings: This framework aims to be sufficiently flexible to be deployed across diverse national settings. Its formulation is important because informal settlements are a permanent fixture of the global urban landscape, and are increasing in scale. Originality/value: Any sustainable strategies to improve informal settlements depend on a better understanding of their urban space, as well as of the producers of this space – the residents themselves. Finally, professional designers may be able to learn from this contemporary urban vernacular grammar – perhaps the only one left in the era of sanitized, contrived and prosaic urban design.